OPTIMAL WAYS TO STRENGTHEN THE SOCIAL PROTECTION OF ORPHANS AND CHILDREN LEFT WITHOUT PARENTAL CARE - Zaitov Elyor Xolmamatovich; Raxmаtullayeva Ozoda Shaxriddinovna (Western European Studies, 2024)
In this article, the authors were concerned with scientifically explaining the optimal ways to strengthen the social protection of orphans and children left without parental care. In the implementation of the social policy of orphans, the importance of their social workers is described in the article.
Keywords: orphan children; social policy; parent; material interest